Single-photon imaging for 3D reflectivity and depth estimation in low-light conditions - Chen, Yi; Zhang, Zhenyu; Wang, Liqiang; Liu, Penghuan; Shi, Yan (Frontiers in Physics, 2025)
Three-dimensional active imaging systems operating in photon-starved regimes have broad applications, including remote sensing, autonomous navigation, and military surveillance. In this study, we present a noncoaxial scanning imaging system capable of generating high-quality depth and reflectivity images with an average of only ∼1 detected photon per pixel, leveraging a single-photon avalanche diode (SPAD) detector. The accompanying depth retrieval algorithm integrates an l1-norm regularizer and operates without requiring prior knowledge of the number of targets in the scene. This design significantly enhances the algorithm’s robustness and reliability for practical applications. Experimental results validate the proposed algorithm’s effectiveness, underscoring its potential for advancing three-dimensional active imaging under photon-starved conditions.